Early-life lessons of the courtship dance in a dance-duetting songbird, the Java sparrow - Soma, Masayo (R Soc Open Sci, 2019)
Vocal learners, such as songbirds, must practise singing in a developmentally sensitive period to master songs. Yet, knowledge remains limited about the development of visual displays in birds, even when courtship includes well-coordinated vocalizations (songs) and body motions. The Java sparrow (Lonchura oryzivora) is a species of songbird that exhibits a courtship duet dancing exchange between the sexes, with this behaviour driving mating success. In this study, juvenile male Java sparrows were observed in captivity, showing that they repeatedly practise the courtship dance in their early life. We called it ‘practice’, as juvenile birds frequently dance towards family members or other juveniles well before sexual maturation. Based on our observation that dance motor performance increased with age, we propose that the practice is needed for motor learning. In addition, it could also be important for establishing vocal-motional coordination or socialization. Older juveniles gradually became capable of singing and dancing simultaneously, and participated in duet dancing more often. We also found that repeated encounters with the same individual promote dance movement. Though our results do not show how much social experiences account for the development of dance communication, early-life dance practising might influence future reproductive success, like song practising does.